2005
DOI: 10.1002/ccd.20437
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel‐eluting stents for the treatment of chronic total coronary occlusions: A strategy of extensive lesion coverage with drug‐eluting stents

Abstract: The recanalization of a chronic total coronary occlusion (CTO) is hampered by a high rate of lesion recurrence. The goal of the present study is to assess the effect of paclitaxel-eluting stents in CTOs in a strategy of extensive stent coverage and the optional use of additional bare metal stents (BMSs). In 82 consecutive patients, a CTO (duration > 2 weeks) was successfully recanalized with implantation of one or more Taxus stents. These patients underwent a repeat angiography after 5.0 +/- 1.5 months and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…Target vessel reocclusion was significantly less frequent with DES vs. BMS in two [19,21] of five studies [6,18,19,21,22] that reported this outcome (odds ratio: 0.29, 95% CI: 0.14, 0.58, P for heterogeneity ¼ 0.16, I 2 ¼ 38%, Fig. 3B).…”
Section: Angiographic Outcomesmentioning
confidence: 76%
See 3 more Smart Citations
“…Target vessel reocclusion was significantly less frequent with DES vs. BMS in two [19,21] of five studies [6,18,19,21,22] that reported this outcome (odds ratio: 0.29, 95% CI: 0.14, 0.58, P for heterogeneity ¼ 0.16, I 2 ¼ 38%, Fig. 3B).…”
Section: Angiographic Outcomesmentioning
confidence: 76%
“…Follow-up angiographic outcomes were reported in 12 studies, including five uncontrolled case series [10,11,13,15,16], five comparative nonrandomized studies [18,19,21,22,27] and in both prospective, randomized controlled trials [6,25] (Table II). The study by Hoye provided angiographic outcomes only for the DES group [27].…”
Section: Angiographic Outcomesmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, DES treatment of the entire segment exposed to pre-dilatation angioplasty may yield greater reductions in restenosis and subsequent TLR than with balloon angioplasty alone or in combination with bare metal stents. 83,87 Nevertheless, percutaneous revascularisation of CTOs is routinely associated with more extensive stent placement. As a consequence, it is unclear whether the improvement in restenosis is offset by a potentially higher risk of thrombotic occlusion, by complications associated with stent fracture or by acquired late malapposition.…”
Section: Contemporary Des Trials In Cto Revascularisationmentioning
confidence: 99%